Number of antenatal care utilization and associated factors among pregnant women in Ethiopia: zero-inflated Poisson regression of 2019 intermediate Ethiopian Demography Health Survey - Mastewal Arefaynie; Bereket Kefale; Melaku Yalew; Bezawit Adane; Reta Dewau; Yitayish Damtie (BMC, 2022)
Plain language summary Antenatal care is among the most effective interventions to mitigate maternal mortality and morbidity. It is an entry point for delivery care, postnatal care and child immunization. This study was conducted to determine the frequency and associated factors of antenatal care utilization in Ethiopia by using 2019 intermediate Ethiopian Demography Health Survey. A cross-sectional study design using secondary data from 2019 intermediate Ethiopian demography and health survey was conducted. 3917 weighted women were included in the study. Recoding, variable generation, labeling and analysis were done by using STATA/SE version 14.0. The objective of this study was to identify the determinants of frequency of antenatal care visit in Ethiopia by using zero inflated Poisson regression. In this study 74.38% of women attend antenatal care at least once during their current pregnancy. Only 41.8% of women use WHO recommended number of antenatal care. Conclusion: maternal age, residence, educational status, household wealth index, religion and region show significant association with the frequency of antenatal care utilization. Advocacy and behavioral change communication should be area of concern for different organizations that are working on antenatal care especially for rural, poor and uneducated women through mass campaign, community dialoging and enhance the effectiveness of health extension programs.